2023
DOI: 10.1002/adma.202301493
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin‐C Activation of Lung Fibroblasts in a 3D Synthetic Lung Extracellular Matrix Mimic

Abstract: The lung extracellular matrix (ECM) maintains the structural integrity of the tissue and regulates the phenotype and functions of resident fibroblasts. Lung‐metastatic breast cancer alters these cell‐ECM interactions, promoting fibroblast activation. There is a need for bio‐instructive ECM models that match the ECM composition and biomechanics of the lung to study these cell‐matrix interactions in vitro. Here, a synthetic, bioactive hydrogel is synthesized that mimics the native lung modulus and includes a rep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…[118][119][120][121][122][123][124] Recently, Kundu and colleagues developed a sophisticated approach to model BC lung metastasis, based on a synthetic biomimetic PEG-hydrogel, functionalized with a peptide mixture to improve adhesion and cell-mediated ECM remodelling. 125 For this purpose, the authors initially identified core adhesion and cleavable peptides present in healthy human lung ECM samples (Fig. 5A).…”
Section: D In Vitro Models Of Breast Cancer Lung Metastasismentioning
confidence: 99%
“…[118][119][120][121][122][123][124] Recently, Kundu and colleagues developed a sophisticated approach to model BC lung metastasis, based on a synthetic biomimetic PEG-hydrogel, functionalized with a peptide mixture to improve adhesion and cell-mediated ECM remodelling. 125 For this purpose, the authors initially identified core adhesion and cleavable peptides present in healthy human lung ECM samples (Fig. 5A).…”
Section: D In Vitro Models Of Breast Cancer Lung Metastasismentioning
confidence: 99%